2016
DOI: 10.15537/smj.2016.8.14654
|View full text |Cite
|
Sign up to set email alerts
|

Family profile of victims of child abuse and neglect in the Kingdom of Saudi Arabia

Abstract: Objectives:To describe the family profile of child abuse and neglect (CAN) subjects in Saudi Arabia.Methods:Data were collected retrospectively between July 2009 and December 2013 from patients’ files, which were obtained from the Child Protection Centre (CPC) based in King Abdulaziz Medical City, Riyadh, Saudi Arabia. Four main sets of variables were examined: demographics of victim, family profile, parental information, and information on perpetrator and forms of abuse.Results:The charts of 220 CAN cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 19 publications
(26 reference statements)
2
37
0
6
Order By: Relevance
“…Para raça/cor, prevaleceu a branca com um total de biente familiar e relatou uma média de idade parecida, que permeava entre 4,61 e 6,72 anos de idade. [14][15][16][17] Sobre a escolaridade das vítimas de violências, a distribuição mais frequente foi o campo 'não se aplica', com 711 casos (43,2%). Este achado justifica-se pela prevalência da distribuição das agressões por faixa etária entre menores não escolarizados, seguida de 218 (13,1%) casos para 5ª a 8ª série incompleta e 138 (8,3%) para ensino médio incompleto.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Para raça/cor, prevaleceu a branca com um total de biente familiar e relatou uma média de idade parecida, que permeava entre 4,61 e 6,72 anos de idade. [14][15][16][17] Sobre a escolaridade das vítimas de violências, a distribuição mais frequente foi o campo 'não se aplica', com 711 casos (43,2%). Este achado justifica-se pela prevalência da distribuição das agressões por faixa etária entre menores não escolarizados, seguida de 218 (13,1%) casos para 5ª a 8ª série incompleta e 138 (8,3%) para ensino médio incompleto.…”
Section: Resultsunclassified
“…21 Um dos fatores que influenciam diretamente essas características e encontrado em análise da situação familiar nos casos de violência doméstica, foi a evidência de que filhos de pai desempregado tinham 2,8 vezes mais chances de serem vítimas de abuso físico. 17 Com base nas variáveis que expressam dados do autor da violência, pode ser analisada a predominância em ambos os sexos, com 35,9% dos casos notificados. Houve atuação de dois suspeitos nos casos de violência e equiparação entre feminino e masculino em casos onde apenas um foi o autor do agravo, com 27,5 e 27,7% dos casos, consecutivamente.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…I read with interest, the recent study on “family profile of victims of child abuse and neglect in the Kingdom of Saudi Arabia” by Alghamdi & Saleheen. 1 Abuse is defined as an act of commission and neglect as an act of omission. This is a pervasive national problem throughout the world with a short and long term physical, mental health, and social consequences to the child, family, and community at large.…”
mentioning
confidence: 99%
“…Thus, one study involving just 5% of all adolescent students in each of five (out of 19) regions in KSA, found 8,978 reported cases of child neglect as compared with a total of 511 such cases registered with the NFSR between 2010 and 2012. Another recent study found that children living in larger households (≥6 members) were 1.5 times more likely to suffer neglect than those in smaller families [14]. Other factors associated with higher levels of neglect include unemployment of the father and single/step-parent households [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%